2022
DOI: 10.1177/15353702211073804
|View full text |Cite
|
Sign up to set email alerts
|

Protective antioxidative and anti-inflammatory actions of β-caryophyllene against sulfasalazine-induced nephrotoxicity in rat

Abstract: The pathogenesis of sulfasalazine (SFZ)-induced nephrotoxicity is unclear. Moreover, there are no reports on the protective effects of β-caryophyllene (BCP) against SFZ-induced renal injury. Hence, in this study, we measured several oxidative stress and inflammatory regulatory molecules alongside the effects of BCP in SFZ-intoxicated rats. Male rats ( n = 48) were distributed to six equal groups as follows: negative control (NC), normal rats treated with low (N-LD; 200 mg/kg/day) and high (N-HD; 400 mg/kg/day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(115 reference statements)
1
11
0
Order By: Relevance
“…In the present study, treatment with BCP resulted in lipid peroxidation mitigation as well as dose-dependent enriched antioxidant capacity, as revealed by lowered MDA and H 2 O 2 and enhanced GPx, SOD, CAT, and GRx activities. These results agree with the previously reported antioxidant capacity of BCP in myocardium [ 16 , 18 ], hepatic [ 48 ], and renal [ 49 ] tissues. Furthermore, treatment with BCP was related with a significant escalation in nuclear translocation of Nrf2, with subsequent HO1 and NQO1 amplification, indicating an intensified Nrf2/HO1/NQO1 signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, treatment with BCP resulted in lipid peroxidation mitigation as well as dose-dependent enriched antioxidant capacity, as revealed by lowered MDA and H 2 O 2 and enhanced GPx, SOD, CAT, and GRx activities. These results agree with the previously reported antioxidant capacity of BCP in myocardium [ 16 , 18 ], hepatic [ 48 ], and renal [ 49 ] tissues. Furthermore, treatment with BCP was related with a significant escalation in nuclear translocation of Nrf2, with subsequent HO1 and NQO1 amplification, indicating an intensified Nrf2/HO1/NQO1 signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, Li et al [ 50 ] reported that BCP enhanced Nrf2 activation in high glucose (HG)-induced glomerular mesangial cells (MCs). Additionally, via activating the Nrf2/HO1 signaling pathway, BCP mitigated focal cerebral ischemia-reperfusion damage [ 20 ], MPTP induced Parkinson’s disease [ 51 ], aflatoxin B1 induced liver toxicity [ 48 ], and sulfasalazine-induced nephrotoxicity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, due to its pleiotropic properties (including anti-diabetic, antitumoral, and anti-allodynic activities), the CB 2 R-mediated therapeutic potential of BCP in the neuroprotection, cardioprotection, hepatoprotection, nephroprotection, and gastroprotection have been demonstrated in many studies [ 47 , 48 , 87 , 98 , 99 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ].…”
Section: β-Caryophyllenementioning
confidence: 99%
“…BCP–CB 2 R interactions trigger several intracellular signallings, including cAMP inhibition, intracellular calcium release, stimulation of SIRT-1/PGC-1α (sirtuin 1/peroxisome proliferator-activated receptor γ coactivator-1α), and AMPK (AMP-activated protein kinase) pathways, as well as mitogen-activated kinase (MAPK) activation [ 42 , 119 , 127 , 128 , 129 ]. Notably, MAPKs can modulate PPAR activity through direct phosphorylation [ 130 ].…”
Section: β-Caryophyllenementioning
confidence: 99%